Endophytic Bacterial Isolates From Halophytes Demonstrate Phytopathogen Biocontrol and Plant Growth Promotion Under High Salinity - Christakis, Christos A. (Front Microbiol, 2021)
Halophytic endophytes potentially contribute to the host’s adaptation to adverse environments, improving its tolerance against various biotic and abiotic stresses. Here, we identified the culturable endophytic bacteria of three crop wild relative (CWR) halophytes: Cakile maritima, Matthiola tricuspidata, and Crithmum maritimum. In the present study, the potential of these isolates to improve crop adaptations to various stresses was investigated, using both in vitro and in-planta approaches. Endophytic isolates were identified by their 16S rRNA gene sequence and evaluated for their ability to: grow in vitro in high levels of NaCl; inhibit the growth of the economically important phytopathogens Verticillium dahliae, Ralstonia solanacearum, and Clavibacter michiganensis and the human pathogen Aspergillus fumigatus; provide salt tolerance in-planta; and provide growth promoting effect in-planta. Genomes of selected isolates were sequenced. In total, 115 endophytic isolates were identified. At least 16 isolates demonstrated growth under increased salinity, plant growth promotion and phytopathogen antagonistic activity. Three showed in-planta suppression of Verticillium growth. Furthermore, representatives of three novel species were identified: two Pseudomonas species and one Arthrobacter. This study provides proof-of-concept that the endophytes from CWR halophytes can be used as “bio-inoculants,” for the enhancement of growth and stress tolerance in crops, including the high-salinity stress.